MODERN STRATEGY OF INTEGRATED PLANT PROTECTION - Pisarenko, V. M.; Kovalenko, N. P.; Pospielova, G. D.; Pischalenko, M. A.; Nechyporenko, N. I.; Sherstiuk, O. L. (Scientific Progress & Innovations, 2020)
The urgency of improving the condition of farm lands today is being solved by effective using fertilizers and environmentally friendly plant protection means, mechanical equipment, introducing the results of selec-tion work and other scientific achievements. The purpose of the study is to determine the peculiarities of the system of integrated plant protection, taking into account their impact on yield environmental safety and soil fertility. As the global tendency favors the eco-balance of plant protection, there is a need for rational using agricultural technologies, which involve achieving a compromise between the desire to obtain a high envi-ronmentally friendly yield and preserve soil fertility. It is the system of organic farming, which is based on the specified complex of organizational, economic, and agro-technical measures and technologies. Peculiar-ities of this system’s technologies, which provide optimization of crops’ phyto-sanitary condition, were de-termined taking into account economic harmfulness levels of pests, diseases and weeds. The role of crop ro-tation as the main agro-technical measure in preventing crop damage by pests incapable of active movement and delaying the settlement of crops by insects, which damage seedlings and migrate from the previous year crop rotation fields, was substantiated. The role of tillage system in weed control was determined taking into account its impact on existing natural systems, creating favorable conditions for plant growth and develop-ment, restoration and preservation of soil fertility. The expediency and peculiarities of using biological (bio-cenotic) method in long-term pest control programs were substantiated. Methods were worked out in detail, which affect the conservation and increase the effectiveness of zoophages’ natural resources: crop rotation, tillage, sowing time, fertilization, weed control, forest-protective belts, using attractive crops, creating fa-vorable conditions for their vital functions, terms and methods of harvesting. The place of chemical method in the system of integrated plant protection and its negative impact on the environment was determined. Measures to optimize the application of chemicals in agro-ecosystems were presented in order to adapt farming systems to the requirements of environmentally friendly food production.